Association of suicide attempts with acne and treatment with isotretinoin: retrospective Swedish cohort study. (11th November 2010) - Sundström, Anders; Alfredsson, Lars; Sjölin-Forsberg, Gunilla; Gerdén, Barbro; Bergman, Ulf; Jokinen, Jussi
Abstract : Objective To assess the risk of attempted suicide before, during, and after treatment with isotretinoin for severe acne. Design Retrospective cohort study linking a named patient register of isotretinoin users (1980-9) to hospital discharge and cause of death registers (1980-2001). Setting Sweden, 1980-2001. Population 5756 patients aged 15 to 49 years prescribed isotretinoin for severe acne observed for 17 197 person years before, 2905 person years during, and 87 120 person years after treatment. Main outcome measures Standardised incidence ratio (observed number divided by expected number of suicide attempts standardised by sex, age, and calendar year), calculated up to three years before, during, and up to 15 years after end of treatment. Results 128 patients were admitted to hospital for attempted suicide. During the year before treatment, the standardised incidence ratio for attempted suicide was raised: 1.57 (95% confidence interval 0.86 to 2.63) for all (including repeat) attempts and 1.36 (0.65 to 2.50) counting only first attempts. The standardised incidence ratio during and up to six months after treatment was 1.78 (1.04 to 2.85) for all attempts and 1.93 (1.08 to 3.18) for first attempts. Three years after treatment stopped, the observed number of attempts was close to the expected number and remained so during the 15 years of follow-up: standardised incidence ratio 1.04 (0.74 to 1.43) for all attempts and 0.97 (0.64 to 1.40) for first attempts. Twelve (38%) of 32 patients who made their first suicide attempt before treatment made a new attempt or committed suicide thereafter. In contrast, 10 (71%) of the 14 who made their first suicide attempt within six months after treatment stopped made a new attempt or committed suicide during follow-up (two sample test of proportions, P=0.034). The number needed to harm was 2300 new six month treatments per year for one additional first suicide attempt to occur and 5000 per year for one additional repeat attempt. Conclusions An increased risk of attempted suicide was apparent up to six months after the end of treatment with isotretinoin, which motivates a close monitoring of patients for suicidal behaviour for up to a year after treatment has ended. However, the risk of attempted suicide was already rising before treatment, so an additional risk due to the isotretinoin treatment cannot be established. As patients with a history of suicide attempts before treatment made new attempts to a lesser extent than did patients who started such behaviour in connection with treatment, patients with severe acne should not automatically have isotretinoin treatment withheld because of a history of attempted suicide.